Influential Factors in Teachers’ Health Education Readiness: A Comparative Study - Mohammed Kadhim Ismael; Mohammed Baqer Habeeb Abd Ali (Migration Letters, 2023)
Background: As per the 2022 report from Diyala’s Directorate of Education in Iraq, 103 elementary schools are operational, catering to the educational needs of approximately 35,000 children on a daily basis. The academic staff, comprising of teachers and administrators across these schools, amounts to a total of 2,944 individuals. Aims: To compare the differences in Cons, Pros, Self-Efficacy, beliefs, and practices for delivering health education. Methods: A descriptive correlational predictive design was used to guide this study. The study was conducted in 103 elementary schools. The study included a simple random sample of 355 elementary school administrators and teachers. The study instrument includes participants’ sociodemographic characteristics, the Elementary Health Education District Assessment Tool. Current Delivery, Stages of Change, Decisional Balance (Pros, Cons), Self-Efficacy, beliefs, and Practices were among the scales and subscales used. Data were collected using a self-reported method. Data were analyzed using the statistical package for social science, version 27. Results: The study results revealed that more than a quarter are in the Maintenance Stage of Change, followed by those who are in the Action Stage of Change, those who are in the Contemplation Stage of Change, those who are in the Preparation Stage of Change, and those who are in the Precontemplation Stage of Change. The study results display that there is a statistically significant difference in the Self-Efficacy for delivering health education between gender groups. Conclusion: The researchers concluded that male teachers are more inclined to use elementary health education than their female counterparts. Teachers who reported that they did not participate in such courses experience greater Cons of using elementary health education. Contrarily, teachers who reported that they participated in such courses enjoy greater Pros of using elementary health education.